KEBIJAKAN PEMERINTAH INDONESIA PASCA KELUAR DARI ROUNDTABLE AND SUSTAINABLE PALM OIL (RSPO) - Angelika, Yoan; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This article will discuss the Indonesian government policy after the exit of the RSPO. RSPO is a non-profit association that unites stakeholders from seven sectors of the palm oil industry - oil palm producers, palm oil processors or traders, consumer goods manufacturers, retailers, banks and investors, NGOs, environmental preservation or conservation, and social NGOs. RSPO with stakeholders aims to develop and implement global standards for sustainable palm oil. But in contrast to the RSPO implementation original destination, RSPO more aligned to consumers than producers of palm oil. Indonesia is the largest palm oil producer in the world, and Indonesia was RSPO can no longer mengakomidir interests of its members. Indonesia itself is officially out of the RSPO was recorded on September 29, 2011, and the government made a policy to establish ISPO in order to realize sustainable palm. ISPO is also expected to bring a positive impact on oil palm plantations Indonesia and Indonesia's CPO production is expected to increase.Keywords: foreign policy, government policy, RSPO, ISPO